Demonstrating Didactic Models for ESD and Bildung in School Education - Shu-Nu Chang Rundgren (Ignatianum University Press, 2023)
Objective of the article: The aim of this article is to synthesise the findings of relevant research articles and to demonstrate several "didactic models" of education for sustainable development (ESD) in school education. Research method: The method of narrative literature review was used to identify didactic models for ESD in school education. A short description of the context of the presented issue: The term didactic refers to the professional scholarship of teaching. In recent decades, the need to develop didactic models that would support school teaching and to allow for this adjustment in new teaching contexts has been addressed. Research has shown that school subject teachers work differently with ESD. It demands holism and pluralism, which requires embracing multiple stakeholders and communities, and a multi-disciplinary approach. Shedding light on achieving sustainability with its holist and pluralist features, this article analyses relevant research articles and demonstrates several "didactic models" for ESD in school education. Conclusions and recommendations: I propose socioscientific issues-based teaching and learning (SSI-TL) as a useful didactic model for ESD and argue for the need to embrace didactic models like SSI-TL in teacher professional development for both pre- and in-service teachers. The article explicitly considers the value of applying Communities of Practice as a theory to guide educational practices and research on education for sustainability in school science. The implications of applying the didactic models presented in the article are relevant not only for ESD, but also for students' development of Bildung to become reflective and responsible citizens.